2019
DOI: 10.1177/1040638719856932
|View full text |Cite
|
Sign up to set email alerts
|

Identification and differentiation of avian Mycoplasma species using MALDI-TOF MS

Abstract: The identification of avian Mycoplasma spp. by conventional immunologic, phenotypic, and molecular methods can be demanding and time-consuming. We evaluated MALDI-TOF MS for its suitability to identify avian mycoplasmas at the species level. We generated a mycoplasma spectral database of 36 main spectrum profiles (MSPs) representing 23 avian Mycoplasma spp. using 23 type and reference strains, 1 live vaccine strain, and 8 clinical isolates. We then used 112 avian Mycoplasma clinical isolates of different avian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Developed MALDI method for rapid screening of avian mycoplasma [114] Various fungi Validation of a free online spectral database for veterinary fungi, 90% matching success [115] MALDI-TOF=Matrix-assisted laser desorption ionization-time of flight tarda isolates were obtained from diseased fish. Then, peptides and proteins were extracted from the bacteria and used to create library reference spectra for identification.…”
Section: Mycoplasmamentioning
confidence: 99%
See 1 more Smart Citation
“…Developed MALDI method for rapid screening of avian mycoplasma [114] Various fungi Validation of a free online spectral database for veterinary fungi, 90% matching success [115] MALDI-TOF=Matrix-assisted laser desorption ionization-time of flight tarda isolates were obtained from diseased fish. Then, peptides and proteins were extracted from the bacteria and used to create library reference spectra for identification.…”
Section: Mycoplasmamentioning
confidence: 99%
“…The work demonstrates conclusively that this organism can be found in pets and thus poses a potential for transmission to humans. Baudler et al [114] reported that diagnosis of avian Mycoplasma by conventional methods can be a time-consuming task fraught with difficulty. Hence, these authors developed a MALDI-TOF Mycoplasma spectral database of 36 main spectrum profiles from 23 avian Mycoplasma spp.…”
Section: Streptococcus Salivarius Streptococcus Equinus Andmentioning
confidence: 99%